Guerra e narrazione autodiegetica nel primo Gadda - Duyck, Mathijs (Incontri. Rivista europea di studi italiani, 2013)
The experience of the Great War is a vital element in Carlo Emilio Gadda’s literary apprenticeship. Although the autobiographical theme of war permeates practically all of Gadda’s writing, it is interesting to note how the author in his fiction effectuates a process of distantiation. An important exception to this tendency are a series of ‘war articles’ which were first published in the newspaper L’Ambrosiano, and which later formed the first part of the short story collection Il castello di Udine (1934). This sequence of five short texts presents an autodiegetic narrator which can be identified with Gadda, and who develops a highly varied discourse on the war he fought, oscillating between essayistic, lyrical and narrative modes. The paper intends to individuate the essential components of Gadda’s autodiegetic war fiction through an intertextual analysis of the author's early works. The surprising intertextual relations between the war articles and the philosophical treatise Meditazione milanese will lead to a reflection on the relation between war experience, gnoseology, ethics and narration of war.